International Conference on Advances in Science, Engineering, Technology and Natural Resources (ICASETNR-16) Nov. 24-25, 2016 P 2016
DOI: 10.15242/iae.iae1116457
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical Profile of Geophagic Clayey Soils Sold in Selected South African Informal Markets

Abstract: Abstract-Geophagia, the intentional ingestion of clayey soil has both useful and negative health effects on humans due to the biomass, physicochemical, mineralogical and geochemical composition of the gritty material. In a few circumstances, clayey soil is viewed as a supplement to health deficiencies resulting from a less than stellar eating routine. Geophagy has been of interest to researchers and analysts due to continued habitual, religious and cultural practices by diverse communities globally in spite of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The slight EC difference between unprepared and prepared near the mine samples may be associated with sieving once fine fractions are more conductive [54], while higher EC results in market samples may be the result of additives (e.g., NaCl) added to geophagic materials, to improve flavor. Other studies reported high EC values in geophagic materials with salt added, and that can be linked to diarrhea-causing enterotoxins absorption and to gastrointestinal epithelium protection [55].…”
Section: Resultsmentioning
confidence: 91%
“…The slight EC difference between unprepared and prepared near the mine samples may be associated with sieving once fine fractions are more conductive [54], while higher EC results in market samples may be the result of additives (e.g., NaCl) added to geophagic materials, to improve flavor. Other studies reported high EC values in geophagic materials with salt added, and that can be linked to diarrhea-causing enterotoxins absorption and to gastrointestinal epithelium protection [55].…”
Section: Resultsmentioning
confidence: 91%